Taijiquan, genius loci and tourism: a participant observation about Chenjiagou - Sergio Raimondo; Laura Rea; Yong-shun Wang (Universidad de León, 2022)
This essay analyses the key concepts enunciated by the international literature on martial arts tourism - and of the even broader category of cultural tourism. It combines notes produced by a participant observation and the images produced by the first author himself. The result is the illustration of a particular case of martial arts tourism included in the decade 2009-2018 and focused on Chenjiagou (Chen village), a village in inland China (Wen county, Henan province, People's Republic of China). Here tourists - attracted by the peculiar spirit of the place, genius loci, expressed in the landscape and in the local customs and reinforced by recurring or occasional celebrations - are contributing to the local economic development and urban improvement, by creating an informal planetary-scale network through the common interest in the martial art of taijiquan.